Transatlantic ‘Positive Youth Justice’: a distinctive new model for responding to offending by children? - Case, Stephen (Crime prevention and community safety, 2018)
A model of ‘positive youth justice’ has been developed on both sides of the Atlantic to challenge the hegemonic punitivity and neo-correctionalism of contemporary actuarial risk-based approaches and the conceptually-restricted rights-based movement of child-friendly justice. This paper examines the origins, main features, guiding principles and underpinning evidence bases of the different versions of positive youth justice developed in England/Wales (Children First, Offenders Second) and the USA (Positive Youth Justice Model) and their respective critiques of negative and child-friendly forms of youth justice. Comparing and contrasting these two versions enables an evaluation of the extent to which positive youth justice presents as a coherent and coordinated transatlantic ‘movement’, as opposed to disparate critiques of traditional youth justice with limited similarities.